Labour regulations in India: Rationalising the laws governing wages - Anwarul Hoda; Durgesh K. Rai (Indian Council for Research on International Economic Relations (ICRIER), 2017)
In this paper, we undertake an evaluation of the laws governing wages in India, identify their shortcomings and offer suggestions for improvement. In doing so, we analyze the provisions in the relevant ILO Conventions and look at the laws and practice in selected developed and emerging countries, and in particular in five comparator countries, which have been successful in industrial development, viz., China, Japan, Malaysia, South Korea and Thailand. The study shows that the wage regulations in India do not measure up to the standards adopted in peer countries and in some respect fall short of the recommendations in ILO Conventions. Some of our laws are very complex and this makes enforcement difficult. The Code on Wages Bill, 2017, seeks to eliminate some of the deficiencies but others will remain outstanding.
Keywords: J31; J33; J38; J780; J880; 330; Labour Regulations; Wages; ILO Conventions; India